Perception of Changes in Spectrum and Envelope of Musical Signals vs Auditory Fatigue - KIN, Maurycy; Dobrucki, Andrzej (Archives of Acoustics, 2016)
The paper presents results of research on an influence of listening fatigue on the detection of changes in spectrum and envelope of musical samples. The experiment was carried out under conditions which normally exist in a studio or on the stage when sound material is recorded and/or mixed. The equivalent level of presented sound samples is usually 90 dB and this is an average value of sound level existing in control room at various recording activities. Such musical material may be treated as a noise so Temporary Threshold Shift phenomenon may occur after several sessions and this may lead to a listening fatigue effect. Fourteen subjects participated in the first part of the experiment and all of them have the normal hearing thresholds. The stimuli contained the musical material with introduced changes in sound spectrum up to ±6 dB in low (100 Hz), middle (1 kHz) and high frequency (10 kHz) octave bands. In the second part of research five subjects listened to musical samples with introduced envelope changes up to ±6 dB in interval of 1 s. The time of loud music exposure was 60, 90 and 120 minutes and this material was completely different from the tested samples. It turned out that listening to the music with an $L_{eq} = 90$ dB for 1 hour influences the hearing thresholds for middle frequency region (about 1–2 kHz) and this has been reflected in a perception of spectral changes. The perceived peaks/notches of 3 dB have the detection ability at 70% and the changes of low and high ranges of spectrum were perceived at the similar level. After the longer exposure, the thresholds shifted up to 4.5 dB for the all investigated stimuli. It has been also found that hearing fatigue after 1 hour of a listening influences the perception of envelope which gets worse of 2 dB in comparison to the fresh-ear listening. When time of listening to the loud music increases, the changes in envelopes which can be detected rise to the value of 6 dB after 90-minutes exposure and it does not increase with further prolongation of listening time.